The Word ‘Over’ As An Adjective In The Corpus Of Contemporary American English - Safitri, Nur Pebriyani; Kurniawaty, Merry (International Journal of Psychosocial Rehabilitation, 2020)
This research is entitled “The Word Over as an Adjective in the Corpus of Contemporary American English: The data were taken from Corpus of Contemporary American English (COCA). The corpus data is a collection of language materials such as a data bank derived from the use of languages  from a variety of sources in highly accessible, novel and academic forms. The objectives of this research are to identify the structure of the word over as an adjective in the COCA and to analyze the meaning of the word over in the COCA. This research used a descriptive method. The theories in research are theories by Greenbaum &Nelson (2000), Huddleston (2002), Downing (2006), Carnie (2007), Morley (2000), Downing (2006). The results of this research show that there are 5 data the word over as an adjective. The results showed that the word ‘over’ has some syntactic behavior. The structure of the word over as an adjective is the word over comes after to be and the meaning of the word ‘over’ is influenced by the behavior of syntax. ‘the word ‘over’ as an adjective mean revealed ends or is completed.